Metacognition and Perspective-Taking in Alzheimer’s Disease: A Mini-Review - Bertrand, Elodie; Landeira-Fernandez, Jesus; Mograbi, Daniel C. (Frontiers in Psychology, 2016)
Metacognition refers to the monitoring and regulation of cognitive processes and its impairment can lead to a lack of self-awareness of deficits, or anosognosia. In the context of different neurological and psychiatric disorders (e.g., traumatic brain injury, dementia, and schizophrenia), studies have shown that patients who present impairments in metacognitive abilities may be able to recognize such difficulties in others and in themselves when exposed to material in a third-person perspective. Considering that metacognitive impairments are an important characteristic of dementia, especially in Alzheimer’s Disease (AD), studies of the relationship between metacognition and perspective-taking may be relevant to improve the quality of life of people with dementia. The current paper first briefly addresses the theme of metacognition and the impact of metacognitive deficits in people with AD. The focus then turns to the relationship between metacognition and perspective-taking in different neurological and psychiatric disorders, particularly AD. This relationship is also discussed based on theoretical models, particularly the Cognitive Awareness Model (CAM). Specifically, the CAM suggests the existence of distinct memory systems for self- and other-information, an idea which is supported by neuroimaging findings. We suggest that the Default Mode Network, as it has been shown to be implicated in self vs. other processing and is affected early in AD, could explain the impact of perspective-taking on awareness of deficits in AD. Finally, we present possible clinical implications of the relationship between metacognition and perspective-taking in AD. Indeed, we considered the possibility of improving patient’s awareness through the use of a third-person perspective, which, consequently, may decrease the negative impacts of anosognosia in AD.